2020
DOI: 10.1021/jacs.0c06000
|View full text |Cite
|
Sign up to set email alerts
|

Charging Organic Liquids by Static Charge

Abstract: Aqueous liquids can be charged effectively by a number of methods for many important applications. Organic liquids, however, cannot be charged effectively by existing methods due to their low conductivities, especially the insulating nonpolar organic liquids; hence, there has not been any significant application developed based on charged organic liquids. This study describes an effective fundamental strategy for charging organic liquids, including nonpolar organic liquids: static charge is simply mixed into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…18,24 It can be explained schematically as Figure 2a. Despite the dispute on charge transfer mechanism in contact electrification, 27,28 we adopted an electron transfer mechanism to explain this result, since the electrified charge quantity is high when using the hydrogel with deionized water. As suggested previously, 5,24,38 the electron transfers between water molecule and the PTFE contribute to the electrified charges.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,24 It can be explained schematically as Figure 2a. Despite the dispute on charge transfer mechanism in contact electrification, 27,28 we adopted an electron transfer mechanism to explain this result, since the electrified charge quantity is high when using the hydrogel with deionized water. As suggested previously, 5,24,38 the electron transfers between water molecule and the PTFE contribute to the electrified charges.…”
Section: Resultsmentioning
confidence: 99%
“…The wide investigations of these dynamic EDL-based electricity generators also draw interest to the mechanism on the origin of surface charges at the liquid/solid interfaces. Even though the Gouy–Chapman–Stern model has been well-established to theoretically describe the structure and the potential drop of the EDL, the origin of the surface charges is still not clearly and comprehensively understood. , Recent studies have found that the contact electrification involved with the electron transfer process at the liquid/solid interfaces contributes to the formation of charged solid surfaces, different from various traditional mechanisms such as ionization, dissolution, or ion adsorption of the solid surfaces. ,,,, Then, Wang’s hybrid EDL model was proposed to describe the two-step formation process of the EDL, based on contact electrification and subsequent electrostatic counterion adsorption. , It is nevertheless noted that there is still argument about the charge transfer mechanism of contact electrification at the solid–liquid interfaces. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some combinations of liquids and charged surfaces (e.g., toluene and PTFE), the transfer was almost complete (i.e., all the static charge on the surface readily transferred to the liquid). 124 However, this direct transfer of charge from the charged surface to the liquid does not always happen. Examples include when the amount of charge on the surface is low or when other materials are used.…”
Section: Fundamentals Of Charge Dissipation Into Liquidmentioning
confidence: 99%
“…In-synthesis doping incorporates dopant atoms into QDs during their formation and is typically achieved using chemical vapor deposition, 39,[42][43][44][45][46][47] plasma synthesis, 37 laser ablation, 48-50 and co-sputtering. [51][52][53][54][55][56][57] Defining the location of the dopant within QDs while using these methods is non-trivial because it strongly depends upon reaction conditions, as well as the material properties of the Si host and chosen dopant. 58 A common challenge known as "self-purification" arises for small (i.e., d < 6 nm) strongly confined QDs that expels dopants to the QD surface during in-synthesis doping.…”
Section: Introductionmentioning
confidence: 99%